Fluorene Removal from Synthetically Concocted Marine Water by Trametes versicolor - Ardag Akdogan, H.; Pazarlioglu, N. (Asian Journal of Chemistry, 2011)
In this study; sub-tropical white rot fungi, Trametes versicolor was investigated for its ability to degrade fluorene in the mediums containing glucose and different concentrations of fluorene (5.0-50.0 mg/L) in batch systems. T. versicolor was also studied for the ability to degrade fluorene in a medium has high saline concentrations. (20, 15, 10, 5, 3.5, 3, 2.5, 1.5 %). Samples were collected at weekly intervals for 6 weeks and fluorene was detected by high performance liquid chromatography. Laccase and Mn peroxidase enzyme activities were also monitored and not detectable at the end of the incubation in higher saline conditions (except 1.5 % salinity). The greatest biodegradation was obtained by T. versicolor with 30.0 mg/L fluorene concentration in 3.5, 3.0, 2.5 and 1.5 % salinity medium.